INTERLANGUAGE ANALYSIS ON STUDENTS’ WRITING ON WHATSAPP APPLICATION IN SECOND LANGUAGE LEARNING: AN ERROR REVIEW (Universitas Pamulang, 2021)
This kind of study was a qualitative content analysis. The purpose of this study was to examine errors that happened during students' written interactions on the Whatsapp application. The data were acquired using purposeful sampling since the researcher identified EFL university students who actively communicated via WhatsApp in written English. The researcher used documentation to collect data for this investigation. To ensure the validity of the data, the researcher took a screenshot of the student's writing that was typed in the Whatsapp group, and interviewed five respondents via Whatsapp voice calls that were recorded using a voice recorder on a smartphone, then transcribed and assessed qualitatively. The researcher collected data in a methodical manner and carried out several data analysis operations like collecting the errors, classifying them, providing and evaluation and explaining the errors and the factors. The researcher concluded from the research findings that both the source language (L1) and the target language (L2) have an effect on students' interlanguage writing output. The study discovered that the native language had an effect on literal translation by utilizing Indonesian grammatical patterns, Indonesian acronyms, omitting plural marker-s, and omitting BE. Meanwhile, the target language's effect was detected by the insertion of auxiliary verbs and the generalization of the past tense –ed.